Selection scheme of mobile sinks in wireless sensor networks - CHENG Long 1; CHEN Can-feng 2; MA Jian 2 (Tongxin xuebao)
Using mobile devices as sinks for efficient data collection in wireless sensor network （WSN）, the architecture of multiple mobile sinks sparse wireless sensor network （M2S2N） was introduced. By taking the ubiquitous nature of mo- bile devices into consideration, different selection schemes of mobile sinks in M2S2N were compared, and an opportunis- tic transmission scheduling algorithm （OTSA） for M2S2N was further proposed. Simulation results indicate that the pro- posed sink selection scheme in OTSA-M2S2N is effective and can significantly improve the performance such as energy efficiency and successful transmission ratio.